The interannual variability of oceanic CO2 parameters in the northeast Atlantic subtropical gyre at the ESTOC site - Santana-Casiano, J. Magdalena; González-Dávila, Melchor; Rueda, María José; Llinás Gonzalez, Octavio; González-Dávila, Enrique Francisco (Global Biogeochemical Cycles, 2007)
The long‐term trends and average seasonal variability in the upper ocean inorganic carbon observations were investigated at the ESTOC Station (the European Time Series in the Canary Islands), on the basis of an existing 10‐year series (1995–2004). Hydrographic temperature and salinity, together with the pH in total scale at 25°C (pHT), total alkalinity (AT), partial pressure of CO2 expressed as fugacity (fCO2), computed dissolved inorganic carbon (CT) and fluxes of CO2 (FCO2) reveal substantial variability over the years. Seasonal detrended data of salinity‐normalized CT (NCT) and experimental fCO2 show upward trends of 0.99 ± 0.20 μmol kg−1 yr−1 and 1.55 ± 0.43 μatm yr−1, respectively, indicating direct control over the CT concentration due to increased atmospheric CO2 concentration. Our series of experimental pHT data confirm the acidification of surface waters in the east Atlantic Ocean, with an interannual decrease of 0.0017 ± 0.0004 pH units yr−1. Interannual trends were examined by determining the variance in biogeochemical anomalies over time. The resulting anomalies in temperature and salinity revealed two scenarios in the ESTOC site, where there are periods of cooler and fresher water than the mean, driven by variations in winter mixed‐layer depths, and periods with inverse temperature and salinity anomaly relationships, related to seasonal changes in the position of the subtropical gyre. Hydrographic and biogeochemical anomalies at ESTOC were linked to large‐scale climate variability indexes, such as the North Atlantic Oscillation (NAO) and the East Atlantic pattern (EA). A delay of around 3 years in the oceanic response to the NAO best correlates with the anomalies observed for temperature (0.83), salinity (0.56), alkalinity (0.49), CT (0.41), fCO2 (0.57) and the depth of the mixed layer (−0.64) with p < 0.05. The seasonal variability and its link‐in to the large‐scale climate variability of the North Atlantic subtropical gyre has been studied using the two long series, BATS and ESTOC. 4,335 Q1 ...